Relationship between left ventricular global longitudinal strain, infarct size and left ventricular function in patients with acute myocardial infarction in a stem cell therapy study. (14th October 2021) - Drabik, L; Mazurek, A; Czyz, L; Skubera, M; Kwiecien, E; Sikorska, M; Kulaga, A; Mikunda, A; Szot, W; Kostkiewicz, M; Brzyszczyk-Marzec, M; Urbanczyk, M; et al.
Abstract: Introduction: It is critically important to determine the accuracy, and relationships between, non-invasive imaging modalities, such as two-dimensional echocardiography (TTE), gated single-photon emission computed tomography (SPECT) and cardiac magnetic resonance imaging (cMRI) in patients with recent acute myocardial infarction (AMI) because these are used as clinical trial endpoints. Modest improvements in the left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV) and infarct zone size (IS) have been reported in AMI stem cells therapy trials (SCT). Purpose: The aim of the study was to evaluate left-ventricular global longitudinal strain (GLS) in patients with AMI enrolled to SCT and assess its relation with infarct zone, LVEF and LVEDV using multimodality imaging including TTE, cMRI and SPECT. Methods: Twenty-eight patients (21 male, 7 female, mean age 60.0±8.7 years) with first AMI, 2–5 days after left anterior descending percutaneous coronary intervention (PCI) and IS ≥10% were enrolled. GLS was evaluated with two-dimensional speckle tracking echocardiography (aCMQ, Philips Epiq 7). Infarct zone was measured using SPECT (E.CAM, Siemens) and gadolinium-enhanced cMRI (Siemens Magnetom Sonata 1.5T). LVEF and LVEDV were assessed with TTE (Auto-ROI, Philips), SPECT (GSQUAN, Siemens) and cMRI (MASS Medis). Measurements were obtained independently by blinded analysts. Results: Mean GLS was −11.0±2.5% and showed a positive correlation with infarct zone by SPECT and MRI, negative with TTE-LVEF and cMRI-LVEF (Figure 1) and borderline with SPECT-LVEF (r=−0.35, p=0.08). There was no correlation between GLS and TTE-LVEDV (r=−0.25, p=0.25); SPECT-LVEDV (r=−0.38, p=0.077) and MRI-LVEDV (r=−0.20, p=0.365). Patients in the third and fourth GLS quartile had a smaller IS measured by MRI and a trend toward a smaller infarct zone by SPECT (table 1). Patients in the GLS fourth quartile had higher TTE-LVEF and a trend toward higher cMRI-LVEF compared with other quartiles. LVEF measured with TTE and cMRI was higher compared with SPECT-LVEF (+2.6±6.8%, p=0.006 and +4.2±7.8%, p=0.030, respectively) with no difference between TTE-LVEF and MRI-LVEF (p=0.823) (Table 1). LVEDV evaluated by SPECT and MRI was higher compared with TTE-LVEDV (+48.3±24.9 ml, +47.7±29.5 ml, both p<0.001) with no difference between SPECT-LVEDV and MRI-LVEDV (p=0.984) Conclusions: In patients with anterior wall AMI, 2–5 days after PCI, GLS showed a good correlation with infarct zone quantified by SPECT and MRI and with LVEF measured with TTE and cMRI. GLS might thus be a valuable tool in the evaluation of myocardial injury in SCT. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): STRATEGMED 265761 "CIRCULATE" National Centre for Research and Development/Poland/ZDS/00564 Jagiellonian University Medical College